Presence of EpCAM‐positive circulating tumor cells as biomarker for systemic disease strongly correlates to survival in patients with hepatocellular carcinoma. Issue 9 (11th June 2013) - Schulze, Kornelius; Gasch, Christin; Staufer, Katharina; Nashan, Björn; Lohse, Ansgar W.; Pantel, Klaus; Riethdorf, Sabine; Wege, Henning
Abstract : Current imaging technologies do not sufficiently detect micrometastasis and therefore do not allow adequate stratification of patients with hepatocellular carcinoma (HCC) for curative or systemic therapy. In HCC, presence of stem cell‐like, epithelial cell adhesion molecule (EpCAM)‐positive cells correlates with tumor aggressiveness and formation of metastasis. Therefore, we investigated the prognostic relevance of EpCAM‐positive circulating tumor cells (CTCs) in patients with HCC. Blood from 78 patients (19 patients in the control cohort and 59 patients with HCC) was tested for CTCs with the CellSearch™ system. Correlation analysis to overall survival (OS), the Barcelona Clinic Liver Cancer (BCLC) staging system, macroscopic and microscopic vascular invasion and alpha‐fetoprotein (AFP) levels were performed. We detected ≥1 CTC in 18/59 HCC patients and in 1/19 patients with cirrhosis or benign hepatic tumor ( p = 0.026). OS was significantly shorter (460 vs . 746 days) in the CTC‐positive cohort ( p = 0.017). Comparing BCLC stages, significant differences in CTC detection rates were also observed: BCLC stages A 1/9, B 6/31 and C 11/19 ( p = 0.006). Ten of 18 patients with macroscopic and 10/16 patients with microscopic vascular invasion exhibited positive findings in CTC testing ( p = 0.004 and p = 0.006). Furthermore, CTC results correlated to AFP (cutoff > 400 ng/mL) levels ( p = 0.050). Our study demonstrates frequent presence of EpCAM‐positive CTC in patients with intermediate or advanced HCC and its prognostic value for OS with possible implications for future treatment stratification. Abstract : What's new? Catching hepatocellular carcinoma (HCC) in its early stages is difficult, and even when detected, the inability to identify early metastatic spread, including micrometastases and potential "metastases‐initiating" circulating tumor cells (CTCs), leaves some patients at high risk of recurrence following curative therapy. One possible means of early metastatic detection may involve stem cell‐like EpCAM‐positive HCC cells, which recently were associated with enhanced tumor growth, high tumorigenic invasiveness, and formation of metastases. In this prospective study, we demonstrate that EpCAM‐positive CTCs frequently are detectable in patients with intermediate or advanced HCC and are strongly correlated with survival.